PENGENALAN DAN PELATIHAN PENGAMBILAN SAMPEL TANAH DISTURBED DAN UNDISTURBED UNTUK SISWA SMK 7 BIDANG KEAHLIAN KONSTRUKSI JALAN, IRIGASI, DAN JEMBATAN - Sulistiawati, Baiq Heny; Harprastanti, Primasiwi; Fatmawati, Leily; Suwarno, Anung; Setyono, Karnawan Joko; Wahyumi, Puji; Sudarmono, Sudarmono; Mahmudi, Wildana Latif (Bangun Rekaprima, 2023)
One of the challenges faced by students from SMK is the learning atmosphere and learning system applied by PTV. This is due to the gap between the SMK curriculum and PTV. State Vocational High School (SMKN) 7 Semarang is one of the vocational schools located in the city of Semarang. SMKN 7 Semarang has 8 expertise competencies, one of which is competence in the field of civil engineering, namely Building Construction, Sanitation and Maintenance (KGSP) and Road, Irrigation, and Bridge Construction (KJIJ). Students of SMKN 7 Semarang already have a basic understanding of civil engineering, but when they enter the PTV world, they still experience difficulties in several fields. Therefore, to bridge and fill the gap from the SMK curriculum to PTV, it is necessary to introduce and train related fields of civil engineering, one of which is field testing. Semarang State Polytechnic as one of the universities has competent human resources to provide solutions to these problems. The PKM team provided introduction and training on the use of hand drill and vane shear tools used for soil testing. The hand drill is used to take disturbed and undisturbed soil samples, while the shear vane is used to determine the shear condition of the soil. After conducting the introduction and training activities, students can better understand how to use the test equipment. In addition, students also understand better in analyzing soil data obtained from testing.